Differential Effects of Dopaminergic Therapies on Dorsal and Ventral Striatum in Parkinson's Disease: Implications for Cognitive Function - Penny A. MacDonald; Oury Monchi (Parkinson's Disease)
Cognitive abnormalities are a feature of Parkinson's disease (PD). Unlike motor symptoms that are clearly improved by dopaminergic therapy, the effect of dopamine replacement on cognition seems paradoxical. Some cognitive functions are improved whereas others are unaltered or even hindered. Our aim was to understand the effect of dopamine replacement therapy on various aspects of cognition. Whereas dorsal striatum receives dopamine input from the substantia nigra (SN), ventral striatum is innervated by dopamine-producing cells in the ventral tegmental area (VTA). In PD, degeneration of SN is substantially greater than cell loss in VTA and hence dopamine-deficiency is significantly greater in dorsal compared to ventral striatum. We suggest that dopamine supplementation improves functions mediated by dorsal striatum and impairs, or heightens to a pathological degree, operations ascribed to ventral striatum. We consider the extant literature in light of this principle. We also survey the effect of dopamine replacement on functional neuroimaging in PD relating the findings to this framework. This paper highlights the fact that currently, titration of therapy in PD is geared to optimizing dorsal striatum-mediated motor symptoms, at the expense of ventral striatum operations. Increased awareness of contrasting effects of dopamine replacement on dorsal versus ventral striatum functions will lead clinicians to survey a broader range of symptoms in determining optimal therapy, taking into account both those aspects of cognition that will be helped versus those that will be hindered by dopaminergic treatment.